Die brief aan Rheginos: Oor geloof en rede en die opstanding - Vorster, W. S. (Hervormde teologiese studies, 1986)
The letter to Rheginos: On faith and reason and the resurrection The article consists of an introduction to and an Afrikaans translation of the Coptic Epistle to Rheginos on the resurrection. It is dedicated to Professor JAAA Stoop as a token of appreciation for his contribution to promote the study of early Christian literature in South Africa.